Cognitive Function in Older Patients with Postherpetic Neuralgia. Issue 1 (23rd May 2013) - Pickering, Gisèle; Pereira, Bruno; Clère, Florentin; Sorel, Marc; de, Geraldine; Navez, Malou; Picard, Pascale; Roux, Delphine; Morel, Véronique; Salimani, Rachida; Adda, Mireille; Legout, Valérie; et al.
Abstract Background and aims Neuropathic pain has been shown to be accompanied by cognitive impairment, but the specific impact of postherpetic neuropathic pain on cognitive processes has not been explored. This study aims to evaluate the impact of pain on several domains of cognition in older patients with postherpetic neuralgia (PHN). Methods This cross‐sectional study (clinicaltrial.gov NCT 00989040) included 84 individuals after signature of informed consent. Participants: 42 patients with PHN and 42 healthy volunteers. Of the 42 PHN patients, 21 received systemic treatment (antidepressants, anticonvulsants, opiates) and 21 had topical treatment with the 5% lidocaine medicated plaster. All participants performed a panel of four cognitive tests: reaction time, semantic memory, decision‐making, and visual memory (Cantab®, Cambridge). Results Forty men and 44 women with a mean age of 72 ± 8 years participated. Each PHN patient was matched by age and gender with a healthy volunteer. Vigilance, decision‐making, and semantic memory were significantly impaired (P < 0.05) in patients on systemic treatment, especially with antidepressants, while no significant changes were noted between the lidocaine plaster group and their matched controls of healthy volunteers. Conclusion This study shows the deleterious effect of systemic PHN treatment on several domains of cognition. Cognitive impairment associated with pain and antidepressants may be reversed by topical pain management. Topical treatment with 5% lidocaine medicated plaster is a valuable alternative for pain alleviation and maintains cognitive integrity in this vulnerable population.